1998
DOI: 10.1152/ajpendo.1998.275.2.e197
|View full text |Cite
|
Sign up to set email alerts
|

Age-related increase in mitochondrial proton leak and decrease in ATP turnover reactions in mouse hepatocytes

Abstract: Age-related changes in mitochondria, including decreased respiratory control ratios and altered mitochondrial inner membrane lipid composition, led us to study oxidative phosphorylation in hepatocytes from old (30 mo) and young (3 mo) male C57BL/J mice. Top-down metabolic control analysis and its extension, elasticity analysis, were used to identify changes in the control and regulation of the three blocks of reactions constituting the oxidative phosphorylation system: substrate oxidation, mitochondrial proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
62
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 46 publications
9
62
0
1
Order By: Relevance
“…Our observation supports a recent report which shows an increase in the in situ oxygen consumption due to proton leak in hepatocytes isolated from young 3 month) and old (30 month) C57BLaJ mice. 32 The results are also consistent with results of Hagen et al 33 who showed a reduced mitochondrial membrane potential in resting hepatocytes from old rats. On facevalue there would appear to be a contradiction, in terms of proton leak, between the in situ and isolated mitochondrial observations.…”
Section: Measuring Proton Leak Rk Porter Et Alsupporting
confidence: 90%
“…Our observation supports a recent report which shows an increase in the in situ oxygen consumption due to proton leak in hepatocytes isolated from young 3 month) and old (30 month) C57BLaJ mice. 32 The results are also consistent with results of Hagen et al 33 who showed a reduced mitochondrial membrane potential in resting hepatocytes from old rats. On facevalue there would appear to be a contradiction, in terms of proton leak, between the in situ and isolated mitochondrial observations.…”
Section: Measuring Proton Leak Rk Porter Et Alsupporting
confidence: 90%
“…47), an increase in mitochondrial proton leak, and a decreased oxygen consumption (25). To address this question, we examined the mitochondrial genome copies relative to nuclear genome, the total cellular oxygen consumption, and cellular ATP content on a per cell basis.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence supports the idea that mitochondria are a major target of the aging process (17, 18). Progressive loss of mitochondrial function is a common feature of aging in several tissues and organisms (19)(20)(21), and accumulation of deletions and point mutations in mitochondrial DNA has been described in aged individuals (22,23). Mitochondrial dysfunction and ROS have been implicated in a wide range of age-related neurodegenerative disorders, including Alzheimer's disease and Parkinson's disease (24,25).…”
mentioning
confidence: 99%